Detection and treatment of omega-3 fatty acid deficiency in psychiatric practice: Rationale and implementation. Issue 1 (December 2016) - Messamore, Erik; McNamara, Robert
Abstract A body of translational evidence has implicated dietary deficiency in long-chain omega-3 (LCn -3) fatty acids, including eicosapenaenoic acid (EPA) and docosahexaenoic acid (DHA), in the pathophysiology and potentially etiology of different psychiatric disorders. Case–control studies have consistently observed low erythrocyte (red blood cell) EPA and/or DHA levels in patients with major depressive disorder, bipolar disorder, schizophrenia, and attention deficit hyperactivity disorder. Low erythrocyte EPA + DHA biostatus can be treated with fish oil-based formulations containing preformed EPA + DHA, and extant evidence suggests that fish oil supplementation is safe and well-tolerated and may have therapeutic benefits. These and other data provide a rationale for screening for and treating LCn -3 fatty acid deficiency in patients with psychiatric illness. To this end, we have implemented a pilot program that routinely measures blood fatty acid levels in psychiatric patients entering a residential inpatient clinic. To date over 130 blood samples, primarily from patients with treatment-refractory mood or anxiety disorders, have been collected and analyzed. Our initial results indicate that the majority (75 %) of patients exhibit whole blood EPA + DHA levels at ≤4 percent of total fatty acid composition, a rate that is significantly higher than general population norms (25 %). In a sub-set of cases, corrective treatment with fish oil-based products has resulted in improvements in psychiatric symptoms without notable side effects. In view of the urgent need for improvements in conventional treatment algorithms, these preliminary findings provide important support for expanding this approach in routine psychiatric practice.